2010
DOI: 10.1364/ol.35.000568
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical circulator designed for operation in a uniform external magnetic field

Abstract: We propose an approach for the design of resonant cavities employed in magnetophotonic crystal (MPC) circulators and isolators. Starting from the analysis of a model circularly symmetric cavity, we show how to obtain a significant splitting of the eigenfrequencies of the two counterrotating cavity modes without introducing subdomains magnetized in opposite directions. Using the multiple-scattering method extended to handle uniaxial gyrotropic materials, we demonstrate numerically an MPC circulator working in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 15 publications
1
71
0
1
Order By: Relevance
“…The isolators using MO photonic crystals require either precise magnetization domain control over micron scale [8] or complex design of photonic crystals [9]. These issues make them difficult to be experimentally realized.…”
Section: Introductionmentioning
confidence: 99%
“…The isolators using MO photonic crystals require either precise magnetization domain control over micron scale [8] or complex design of photonic crystals [9]. These issues make them difficult to be experimentally realized.…”
Section: Introductionmentioning
confidence: 99%
“…We find ω ∝ i , and thus is proportional to the magnetization M. To achieve large ω (∼ω 0 i / r ), a magnetic domain engineering is generally needed [25]. To avoid the magnetic domain engineering while still achieving large frequency splitting, one can nevertheless design a more sophisticated resonator and thus using uniform magnetization [26].…”
Section: A Magneto-optical Resonatormentioning
confidence: 92%
“…It was reported that with increasing the amount of Bi substitution for rare-earth element, FR of Bi:RIG becomes large [2]. Bi:RIG have been used for magneto-optical device elements in such as magnetoplasmonic structure [3,4], optical isolators [5], circulators [6], and magnet photonic crystals (MPCs) used in magneto-optic spatial light modulators (MOSLMs) [7]. Among them, bismuth substituted gadolinium iron garnet (Bi:GdIG) is one of the ferrimagnetic rate-earth iron garnets showing perpendicular magnetic anisotropy [8,9].…”
Section: Introductionmentioning
confidence: 99%